2023
DOI: 10.1002/sstr.202300282
|View full text |Cite
|
Sign up to set email alerts
|

2D Material‐Based Wearable Energy Harvesting Textiles: A Review

Iftikhar Ali,
Marzia Dulal,
Nazmul Karim
et al.

Abstract: Wearable electronic textiles (e‐textiles) have emerged as a transformative technology revolutionizing healthcare monitoring and communication by seamlessly integrating with the human body. However, their practical application has been limited by the lack of compatible and sustainable power sources. Various energy sources, including solar, thermal, mechanical, and wind, have been explored for harvesting, leading to diverse energy harvesting technologies, such as photovoltaic, thermoelectric, piezoelectric, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 626 publications
0
8
0
Order By: Relevance
“…Other materials, such as transition metal dichalcogenides (TMDs), black phosphorus (BP), phosphorene, hexagonal boron nitride (h-BN), and MXene, have been employed in various functions within SCs due to their functionalization and bandgap re-engineering capabilities . These materials have been utilized as absorber layers, charge transport layers, blocking layers, surface passivators, heterojunction components, catalysts, and as electrodes.…”
Section: Layers and Materials For Scsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other materials, such as transition metal dichalcogenides (TMDs), black phosphorus (BP), phosphorene, hexagonal boron nitride (h-BN), and MXene, have been employed in various functions within SCs due to their functionalization and bandgap re-engineering capabilities . These materials have been utilized as absorber layers, charge transport layers, blocking layers, surface passivators, heterojunction components, catalysts, and as electrodes.…”
Section: Layers and Materials For Scsmentioning
confidence: 99%
“…There are different types of modern techniques developed to harvest ambient renewable energy, including triboelectricnanogenerators, piezoelectric nanogenerators, and magnetoelastic generators for mechanical energy conversion, pyroelectric generators (PEG) and thermoelectric generators (TEG) for harvesting ambient thermal energy . , Especially, these modern mechanical energy harvesting techniques are increasingly gaining popularity due to their ability to harvest a variety of energy forms from the environment including human motions (walking, breathing, heartbeat pulse, etc. ), vibration, flowing water, raindrops, wind, and waste heat. …”
Section: Renewable Energy Harvestersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, conductive inks are widely used for the fabrication of a broad range of devices for specialized applications, from sensors, integrated circuits, wearable electronics, radiofrequency identification tags, to energy harvesting/storage systems [9,10,[13][14][15][16][17][18][19]. For example, Barmpakos et al [9,10] showed that commercial graphene and f -rGO [6] can perfectly act as temperature sensors as well as heaters with a stable response and durability to thermal stressing for ink-jet printed devices.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable electronic textiles (e‐textiles) and the Internet of Things (IoT) have encouraged extraordinary developments, stimulating advances in biosensors, smart wearable systems, and cutting‐edge solutions for healthcare and portable electronics 1–3 . The rise in the number of sensors in e‐textile devices promptly correlates with an increase in power demand.…”
Section: Introductionmentioning
confidence: 99%